New visions of optical soliton to a class of generalized nonlinear Schrödinger equation with triple refractive index and non-local nonlinearity - Elsonbaty, Nivan M.; Badra, Niveen M.; Ahmed, Hamdy M.; Alkhatib, Soliman; Elsherbeny, Ahmed M. (Ain Shams Engineering Journal, 2024)
Because it is used in communication and information technology, the propagation of pulses in optical fibers has become a significant research subject in recent years. Mathematical models have been created to describe the behaviors of optical solitons in optical fibres, such as the Kaup-Newell equation, the nonlinear Schrödinger equation with various types of nonlinearity, and others. A model among these is the newly generalized nonlinear Schrödinger equation with triple refractive index and non-local nonlinearity. To secure optical solitons for a particular case of this novel model, we used the improved modified extended tanh function approach. Different solutions have been acquired such as bright solitons, dark solitons, singular solitons, singular periodic solutions, trigonometric solutions, and hyperbolic solutions. Some of the discovered solutions are shown in 2D and 3D graphs for better comprehension and demonstration.